2021
DOI: 10.1088/1367-2630/abef28
|View full text |Cite
|
Sign up to set email alerts
|

An ultrawide-zero-frequency bandgap metamaterial with negative moment of inertia and stiffness

Abstract: Metamaterials have demonstrated great potential for controlling wave propagation since they are flexibly adjustable. A new one-dimensional metamaterial model with both a negative effective moment of inertia and negative effective stiffness is proposed. A negative effective moment of inertia and negative effective stiffness can be achieved by adjusting the structural parameters in certain frequency ranges. Bandgaps in the low-frequency range with exponential wave attenuation can be generated in the metamaterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Liu et al [24] presented an I-shaped radial elastic metamaterial and found that the material can generate ultra-low-frequency wide bandgaps under quasi-static conditions. Moreover, Bae [37], Yang [38], Bera [39], and Muhammad [40] et al have investigated the influence of geometric and material parameters on bandgap properties. Gerard [41], Zhao [42], and De Ponti [43] proposed 3D metamaterial structures and proved that three-dimensional structures can also be adjusted to generate ideal bandgaps, and their findings are helpful when considering the vibration suppression of metamaterials in low-frequency bands.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [24] presented an I-shaped radial elastic metamaterial and found that the material can generate ultra-low-frequency wide bandgaps under quasi-static conditions. Moreover, Bae [37], Yang [38], Bera [39], and Muhammad [40] et al have investigated the influence of geometric and material parameters on bandgap properties. Gerard [41], Zhao [42], and De Ponti [43] proposed 3D metamaterial structures and proved that three-dimensional structures can also be adjusted to generate ideal bandgaps, and their findings are helpful when considering the vibration suppression of metamaterials in low-frequency bands.…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Wang. [ 36 ] proposed a new 1D metamaterial model with both a negative effective moment of inertia and negative effective stiffness. Lin et al [ 37 ] proposed metamaterial which exhibits a quasi‐static bandgap and negative effective stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…As significant advances in engineering structures, metamaterials have attracted increasing attention for their applications in controlling wave propagation and vibration reduction [1][2][3]. Metamaterials are composed of artificial periodic structures that are designed to achieve novel physical properties, such as an effective negative mass [4][5][6], negative refraction [7,8] and topological effects [9,10].…”
Section: Introductionmentioning
confidence: 99%